Hybridisation and transmedia narratives in contemporary popular music. The case of the virtual band Gorillaz. - Pérez-Ordóñez, Cristina de los Ángeles; Castro-Martínez, Andrea; Torres-Martín, José Luis (My University, 2023)
The virtual band Gorillaz has become a reference in the music industry by mixing virtuality and presence in all its expressions (Jeffery, 2017). Indeed, this gang is presented as a group of four cartoons whose image has no reference to the real world or to fantasy, but is shown as a set of symbols through which the band manifests its identity (Prior, 2009). This band has since its inception shown itself to audiences through multiple identities based on intertextual references and postmodern popular culture names (Rambarran, 2016). The multiplicity of identities together with the diversity of animation formats and projection constitutes the essence of this visual and musical project. This paper aims to determine the band's transmedia narrative, as well as the multiple hybridisations of formats that are shown in the recorded formats and the performances. We focus on the analysis of their new album, Cracker Island (2023), whose narrative moves from virtual to physical spaces. Thus, through a visual and narrative analysis, we study the transmedia narrative on digital platforms, from December 2022 to February 2023. It also includes an analysis of three music videos and completes with a study of the band's launch performance for the Skinny Ape track, held in London and New York. At this event, the band had the collaboration of Google who developed an app where attendees could watch "Gorillaz play in real life as Murdoc, 2D, Noodle and Russel literally tower above them, playing in the middle of two of the world's most iconic skylines" (Mondosonoro, 2022). The findings evidence the storytelling of transmedia and a unique visual universe that connects with audiences, as well as highlight the possibilities of audiovisuals for contemporary music industries, such as video-volumetric (VV), immersive virtual environments (IVEs) and virtual intelligence or augmented reality, both for recorded and live formats.
Keywords: Música - Efectos de las innovaciones tecnológicas; Realidad virtual en la música; Gorillaz; Augmented reality; Virtual band; Visual storytelling; Music